A rare case of coexistence of autoimmune polyglandular syndrome type 3 with growth hormone deficiency and hyperthyroidism in a patient with pseudo-Turner's syndrome. Issue 10 (October 2020) - Zhou, Weibin; Lin, Haiyang; Chen, Min; Ning, Jianwen
Autoimmune polyglandular syndrome (APS) is a rare disease that is characterized by autoimmune reactions to multiple endocrine and non-endocrine organs, which can be divided into four main types. The principal manifestations of APS-3 are autoimmune thyroid disease and other autoimmune diseases, such as type 1 diabetes, atrophic gastritis, pernicious anemia, vitiligo, alopecia, and myasthenia gravis, but not Addison's disease or hypoparathyroidism. Here we report a case demonstrating the rare coexistence of growth hormone deficiency and hyperthyroidism with sexual dysgenesis, secondary amenorrhea, cardiomegaly, splenomegaly, hypoproteinemia, pleural effusion, seroperitoneum, pericardial effusion, anasarca, osteoporosis, vitamin D deficiency, iron-deficiency anemia, poor blood coagulation, leucocytopenia, peripheral neuropathy, hyperuricemia, ichthyosis, tinea cruris, and onychomycosis.